Respuestas

2012-08-08T15:54:57+02:00

hay que sacar por la formula

x=-b+-√b^2 -4ac

    _____________

          2a

entonces

    -12+-√144-(4)(7)(-3)

 x=________________

             14

  

      -12+-8√2

x=   _______

           14

 

       2(-6+4√2)

x1=   ________

           14

simplificas 2 con el 14

 

                            -6+4√2

respuesta     x1=    _____

                                 7

      -12-8√2

x2= ______

          14

 

                           -6-8√2

respuesta     x2=   _____

                              7